Analisa Dan Perancangan Sistem Informasi Kepegawaian Di UPTD BSPM Provinsi Banten - Fanny Fransisca (ISB Atma Luhur, 2013)
As the development of information technology, the more influence on a variety of organizations and agencies, especially the world of work environment in which there were kinds of data processing, that was difficult if only done by a manual system or the systems that were classified into non effective system. Nowadays, UPTD BSPM Banten province has been applied for non effective system. Despite of its data processing already used computer but the application was microsoft office. As the solution of these problems required an effective system that was Human Resources Information System that will provide better performance in data processing at UPTD BSPM Banten Province. By the existence of the system, it will provide even more comfort in the process of data processing and it also provides information services fast, precise and accurate.